The Role of Christian Education in Developing Responsible Digital Literacy Among Adolescents - Sugihyono Sugihyono (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2025)
This study explores the role of Christian education in developing responsible digital literacy among adolescents. In the digital age, where the pervasive use of technology presents both opportunities and challenges, the need for ethical guidance in navigating the online world is crucial. Christian education, with its emphasis on values such as honesty, responsibility, and empathy, provides a moral foundation that can help adolescents engage with technology in an ethical manner. Through qualitative research, including in-depth interviews and observations, this study identifies how Christian teachings influence adolescent attitudes toward digital use, highlighting the importance of integrating digital literacy into religious education. The findings suggest that Christian education significantly enhances adolescents' awareness of the ethical implications of their online behaviors, fostering a more responsible approach to technology use. The study concludes with recommendations for strengthening the digital literacy curriculum in Christian educational institutions and for training educators to better guide adolescents in making responsible digital choices. These efforts can contribute to the development of a more ethical and conscientious generation of digital users.